Dual-Drug Containing Core-Shell Nanoparticles for Lung Cancer Therapy. Issue 1 (December 2017) - Menon, Jyothi; Kuriakose, Aneetta; Iyer, Roshni; Hernandez, Elizabeth; Gandee, Leah; Zhang, Shanrong; Takahashi, Masaya; Zhang, Zhang; Saha, Debabrata; Nguyen, Kytai
Abstract Late-stage diagnosis of lung cancer occurs 95% of the time due to late manifestation of its symptoms, necessitating rigorous treatment following diagnosis. Existing treatment methods are limited by lack of specificity, systemic toxicity, temporary remission, and radio-resistance in lung cancer cells. In this research, we have developed a folate receptor-targeting multifunctional dual drug-loaded nanoparticle (MDNP) containing a poly(N-isopropylacrylamide)-carboxymethyl chitosan shell and poly lactic-co-glycolic acid (PLGA) core for enhancing localized chemo-radiotherapy to effectively treat lung cancers. The formulation provided controlled releases of the encapsulated therapeutic compounds, NU7441 - a potent radiosensitizer, and gemcitabine - an FDA approved chemotherapeutic drug for lung cancer chemo-radiotherapy. The MDNPs showed biphasic NU7441 release and pH-dependent release of gemcitabine. These nanoparticles also demonstrated good stability, excellent hemocompatibility, outstandingin vitro cytocompatibility with alveolar Type I cells, and dose-dependent caveolae-mediatedin vitro uptake by lung cancer cells. In addition, they could be encapsulated with superparamagnetic iron oxide (SPIO) nanoparticles and visualized by MRIin vivo . Preliminaryin vivo results demonstrated the low toxicity of these particles and their use in chemo-radiotherapy to effectively reduce lung tumors. These results indicate that MDNPs can potentially be used as nano-vehicles to provide simultaneous chemotherapy and radiation sensitization for lung cancer treatment.